Motivation and Retention of Physicians in Primary Healthcare Facilities: A Qualitative Study From Abbottabad, Pakistan - Sayed Masoom Shah; Shehla Zaidi; Jamil Ahmed; Shafiq Ur Rehman (Kerman University of Medical Sciences, 2016)
Background: Workforce motivation and retention is important for the functionality and quality of service delivery in health systems of developing countries. Despite huge primary healthcare (PHC) infrastructure, Pakistan's health indicators are not impressive; mainly because of under-utilization of facilities and low patient satisfaction. One of the major underlying issues is staff absenteeism. The study aimed to identify factors affecting retention and motivation of doctors working in PHC facilities of Pakistan. Methods: An exploratory study was conducted in a rural district in Khyber Puktunkhwa (KP) province, in Pakistan. A conceptual framework was developed comprising of three organizational, individual, and external environmental factors. Qualitative research methods comprising of semi-structured interviews with doctors working in basic health units (BHUs) and in-depth interviews with district and provincial government health managers were used. Document review of postings, rules of business and policy actions was also conducted. Triangulation of findings was carried out to arrive at the final synthesis. Results: Inadequate remuneration, unreasonable facilities at residence, poor work environment, political interference, inadequate supplies and medical facilities contributed to lack of motivation among both male and female doctors. The physicians accepted government jobs in BHUs with a belief that these jobs were more secure, with convenient working hours. Male physicians seemed to be more motivated because they faced less challenges than their female counterparts in BHUs especially during relocations. Overall, the organizational factors emerged as the most significant whereby human resource policy, career growth structure, performance appraisal and monetary benefits played an important role. Gender and marital status of female doctors was regarded as most important individual factor affecting retention and motivation of female doctors in BHUs. Conclusion: Inadequate remuneration, unreasonable facilities at residence, poor work environment, political interference, inadequate supplies, and medical facilities contributed to lack of motivation in physicians in our study. Our study advocates that by addressing the retention and motivation challenges, service delivery can be made more responsive to the patients and communities in Pakistan and other similar settings.